Recent insights from human induced pluripotent stem cell models into the role of microglia in amyotrophic lateral sclerosis - Nikel, LM; Talbot, K; Vahsen, BF (Wiley, 2024)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease, primarily leading to the degeneration of motor neurons. The traditional focus on motor neuron-centric mechanisms has recently shifted towards understanding the contribution of non-neuronal cells, such as microglia, in ALS pathophysiology. Advances in induced pluripotent stem cell (iPSC) technology have enabled the generation of iPSC-derived microglia monocultures and co-cultures to investigate their role in ALS pathogenesis. Here, we briefly review the insights gained from these studies into the role of microglia in ALS. While iPSC-derived microglia monocultures have revealed intrinsic cellular dysfunction due to ALS-associated mutations, microglia-motor neuron co-culture studies have demonstrated neurotoxic effects of mutant microglia on motor neurons. Based on these findings, we briefly discuss currently unresolved questions and how they could be addressed in future studies. iPSC models hold promise for uncovering disease-relevant pathways in ALS and identifying potential therapeutic targets.